Challenges and prospects of the green ecology in Kazakhstan based on international experience - Ainur Seilkhan; Akbota Beken; Zhang Shicheng; Gau Siyau Jiang; Madina Yussubaliyeva; Zhanat Idrisheva; Manira Zhamanbayeva; Almira Bukunova (Caspian Journal of Environmental Sciences)
From the point view of sustainable development, there is no conflict between economic growth and the preservation and improvement of the environment. In fact, the realization of the goals of sustainable development by institutionalizing a wise and sustainable view of activities in different economic, social, cultural and political dimensions, including paying attention to the sustainability of planning in the environmental sector is realized in the light of optimal consumption of resources and environmental protection. Therefore, the creation of suitable platforms for improving productivity, quality, competitiveness, creativity, and innovation in the use of optimal materials and benefiting from the favorable environment along with economic and social growth indicators can be achieved through the establishment of the green management system at the country level and finally, the implementation and it is possible to implement a green government. Achieving sustainable and economic development goals emphasizes the necessity of carefully consuming the country's natural resources. According to the studies conducted to establish the green government system in institutions and organizations, the existing challenges can be examined from three general aspects: managerial problems and obstacles at the country level, technical and cultural issues, and obstacles. The establishment of the green government in the country's management system has not been followed seriously, and the need to implement it and provide correct management solutions at the macro level of the country and the micro level in the institutions and organizations has yet to be considered. From a technical point of view, the lack of required knowledge in optimizing material and energy consumption, especially in the implementation sector, and the lack of sufficient specialists in this field are important limitations. At the end, the managers' lack of vision and accountability regarding the need to preserve the country's resources and reserves as well as the lack of necessary knowledge and training in establishing the mentioned system play an essential role in the lack of access to the abovementioned goals. The obtained results show that the concept of green ecology is a multidisciplinary research field, using the planning method supported by decision-making tools capable of modeling green infrastructure as an ecological network formed by natural and semi-natural areas to equally distribute public services for increasing the quality of life as well as a wide range of ecosystem services and sustainability in communities.